KIAI MUHAMMAD ZAINUDDIN ABDUL MADJID DAN PERGULATAN POLITIK NAHDLATUL WATHAN DI LOMBOK 1953-1977 - Asmaul Husna Wachid (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2019)
Abstract: This article discusses the politics of Nahdlatul Wathan in Lombok which is led by Kiai Zainuddin. This study uses descriptive qualitative research with historical approaches, sociological approaches, and political approaches. The research method used is divided into four stages, namely heuristics, historical criticism, interpretation, and historiography. The research data was obtained from the process of reviewing and analyzing data that can be trusted for authenticity in the form of written sources or the results of interviews that have been conducted. The analysis of the data obtained can be concluded that Tuan Guru Kiai Haji Muhammad Zainuddin Abdul Madjid is one of the sons of Tuan Guru Abdul Madjid in Lombok and the best student who graduated from Madrasah Ash-Shaulatiyah in Mecca. He became a community leader and a cleric who was able to purify Islamic teachings by establishing many madrassas for the people of Lombok. The participation of Tuan Guru Kiai Haji Muhammad Zainuddin Abdul Madjid in the political arena is none other than to achieve the goals that must be achieved by the Nahdlatul Wathan organization, one of which is for the welfare of Muslims in Indonesia, especially on the island of Lombok. The role of Tuan Guru Kiai Haji Muhammad Zainuddin Abdul Madjid in the political struggle is as a consolidator, educator, mobilizer, and political mediator for followers of Nahdlatul Wathan and people outside Nahdlatul Wathan. Keywords: Kiai Zainuddin, political, Nahdlatul Wathan, Lombok